2022
DOI: 10.1111/rda.14250
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Holstein cows and heifers submitted to timed artificial insemination and receiving one or two doses (12 h apart) of semen

Abstract: The objective of this retrospective study was to assess the effect of receiving a single (n = 50,285) or double (n = 4392) artificial insemination (AI), 12 h apart, within a timed artificial insemination protocol on pregnancy per AI (P/AI) in nulliparous heifers (inseminated with either sex-sorted or conventional semen) and pluriparous Holstein cows in a commercial dairy herd. Also, this study aimed to investigate the relationship between temperature-humidity index (THI) and time of the first AI and fertility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A recent study of pregnancy loss in New Zealand compared with North American Holsteins showed a higher abortion rate in the latter genotype, with an interaction between parity and genotype (Garzón et al, 2022). Additionally, Melendez et al (2023) found lower late embryo mortality (32 to 53 days) in Holstein cows sired by Limousine, compared with Holstein sires.…”
Section: Risk Factors For Abortionmentioning
confidence: 97%
“…A recent study of pregnancy loss in New Zealand compared with North American Holsteins showed a higher abortion rate in the latter genotype, with an interaction between parity and genotype (Garzón et al, 2022). Additionally, Melendez et al (2023) found lower late embryo mortality (32 to 53 days) in Holstein cows sired by Limousine, compared with Holstein sires.…”
Section: Risk Factors For Abortionmentioning
confidence: 97%
“…Melendez et al. (2023) reported a significant difference in late embryo mortality (32–53 days of gestation) in Holstein cows bred with either Holstein or Limousin semen (15.2% and 9.8%, respectively), and this result was attributed to hybrid vigor in the crossbred calf.…”
Section: Genetic Variability In Cattle Breeds For the Risk Of Abortio...mentioning
confidence: 99%
“…Additionally, the training of inseminators is a significant contribution to the successful commercial application of AI to dairy cattle breeding [ 12 , 13 ]. In consequence, inseminator training and improvements in the act of inseminating remain topics of great interest [ 14 , 15 , 16 , 17 ]. However, the correct detection of estrus remains a challenge [ 18 , 19 , 20 , 21 , 22 ] determining that some 20% of inseminations may be performed in pregnant cows [ 21 ].…”
Section: Introductionmentioning
confidence: 99%